Physical and Mental Health Status in Toxoplasma-Infected Women before and 3 Years after They Learn about Their Infection: Manipulation or Side-Effects of Impaired Health? - Šebánková, Blanka; Flegr, Jaroslav (Frontiers in Ecology and Evolution, 2017)
Latent toxoplasmosis is known to be associated with specific changes in animal and human behavior and human personality. Many toxoplasmosis-associated shifts, such as an extroversion-introversion shift or a trust -suspicion shift, go in opposite directions in men and women. The stress coping hypothesis suggests that such behavioral effects of toxoplasmosis are side effects of chronic stress caused by lifelong parasitosis and associated health disorders. Several studies have searched for, and typically found, indices of impaired health in infected subjects. However, subjects were always aware of their toxoplasmosis status, which could influence obtained data and cause false-positive results of the studies. Here we searched for differences in physical and mental health status among 39 Toxoplasma-infected and 40 Toxoplasma-free female university students who completed identical questionnaires (N-70, and anamnestic questionnaire), before and 3 years after they were informed of their toxoplasmosis status. Our results showed that infected women showed indices of poorer health status, not only after, but also before they were informed of their infection. In accordance with previously published data, these indices were more numerous and stronger in Rh-negative than in Rh-positive women. Present results suggest that observed indices of poorer health and symptoms of chronic stress in Toxoplasma-infected subjects are real. Due to its high (30%) prevalence, toxoplasmosis could represent an important factor for public health.